Instructional leadership practices of the secondary school heads in the division of Pangasinan I - Nicolas, Nora F. (San Carlos City, Pangasinan : [s.n.], 2015)
This study focused on the level of instructional leadership practices of the secondary school heads in the Division of Pangasinan I as perceived by themselves and the education program supervisors. Specifically, it determined the profile of the respondents, their level of instructional leadership practices, and the significant difference between the respondents own perception and the perception of the education program supervisors in order to come up with an information material. The descriptive method of research was used in this study. Survey questionnaire was utilized as the main instrument to support and further verify the information gathered. Moreover, the respondents of the study were the 113 secondary school heads and nine (9) education program supervisors in the Division of Pangasinan I. Frequency counts, percentage, average weighted mean and z-test were used for statistical evaluation of data. Findings revealed that as to the profile of the respondents: with respect to highest educational attainment, 36 out of 113 or 31.9% of the school head respondents have finished their master's degree; 19 or 16.8% have already finished their doctoral degree; 26 or 23% have finished master's degree with doctoral units; and 32 or 28.3% were BSE graduates with earned master's units. With respect to the number of years as school head, almost a half or 49 out of 113 or 43.5% of the school heads have 10-15 years of leading the schools. And with respect to the in-service trainings attended, all of them were recipients of in-service trainings especially in the division level which remarkably indicates a 100% attendance. The level of instructional leadership practices of the school heads is very satisfactory with a grand total overall average weighted mean of 4.05. There is no significant difference between the secondary school heads and the education program supervisors' perception on the level of instructional leadership practices with the computed - values are lower than the tabular value of 1.96 at .05 level of significance. It is concluded that majority of the secondary school heads have pursued their graduate studies, most of them are already in the highest position of a principal, and their participation in in-service trainings indicates very high percentage. The secondary school heads have very satisfactory level on their instructional leadership practices as enunciated under RA 9155. The secondary school heads and the education program supervisors have the same perception on the level of instructional leadership practices. In the light of the conclusions, it is recommended that the school heads should continuously uphold the importance of upgrading themselves through graduate schooling and providing themselves enough training to keep abreast the needs of a dynamic and learning society. The secondary school heads in the Division of Pangasinan I should endeavor to reach the level of outstanding in order to achieve high quality education and desired excellence. The proposed information material should be utilized as a guide for their continuous professional improvement and growth until they have developed the needed skills and be able to reach the highest or outstanding level. Similar studies should be conducted in the future using the same variables and other variables pertaining to instructional leadership practices but of different subjects.
Bibliography: pages 152-157.
CHED-La Union
Keywords: School -- Administration